Perlindungan Hukum Terhadap Investor Akibat Praktik Manipulasi Dalam Pasar Modal - Ida Ayu Cintiya Kencana Dewi; I Nyoman Putu Budiartha; Ni Made Puspasutari Ujianti (Fakultas Hukum Universitas Warmadewa, 2021)
The existence of manipulation practices in the capital market that harm investors are an event that requires legal protection. Investors and the public need to know more about market manipulation in the capital market. Market manipulation is one of the capital market's most heinous crimes. The subject addressed in this thesis is how to govern capital market manipulation tactics for investors. Furthermore, what legal protection does an investor have in the event of stock market manipulation? The research utilized is normative legal research, which looks at written legislation from a variety of perspectives but does not look at how it is applied or implemented. With normative legal research types, to collect legal sources, the authors undertake research using materials in the form of primary, secondary, and tertiary legal materials. This study concludes that market manipulation is an activity carried out to create a false picture of trading activities and prices in the stock exchange. This activity is usually carried out by individuals in the capital market who aim to influence stock prices and disseminate incomplete information. Preventive and repressive legal protection are two options for legal protection. While in repressive legal protection, meaning litigation, non-litigation, and sanctions, preventive legal protection is carried out by giving public education and oversight by the OJK on transactions.